Examining the socio-economic effects of teenage pregnancy: A Case study of Manya Krobo Municipality of Ghana - Agyemang, Nathan Asamoah (Research Journal in Advanced Social Sciences, 2020)
The prevalence of teenage pregnancy has become very common in the Ghanaian society, especially among the youth who are at the primary and junior high school (JHS) level of education. The study assessed the prevalence of teenage pregnancy with the challenges faced by teenage pregnant mothers in the Manya Krobo Municipality of Ghana. It also assessed the effects of teenage pregnancy on the socio-economic development and well-being of the society. The results revealed that societal rejection was the major socio-economic challenge faced by pregnant teenagers. Based on the findings, the study concluded that financial dependence on society and involvement in social vices were the major effects of teenage pregnancy.